Compaction of quartz-kaolinite powders with aggregated initial microstructure - Elastic properties and anisotropy - Beloborodov, R.; Pervukhina, Marina; Esteban, L.; Lebedev, Maxim (2015)
The effects of compaction on elastic properties of shales and their anisotropy are important for seismic imaging, seismic to well tie and borehole stability issues. Compaction affects microstructure and as a consequence all the physical properties of shales including their elastic moduli, electrical conductivity and permeability. The results of this experimental study of compacted artificial shales allow to conclude that elastic anisotropy grows with increase of quartz amount and during porosity reduction. At a given porosity, the increase of the quartz fraction results in higher ultrasonic velocities. The anisotropy of P-waves does not depend on quartz grains orientation. There is a necessity to further investigate the relationships between the microstructural properties and the physical properties of these artificial shales.